Harvey Milk at Gay Pride San Jose - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Harvey Milk with three other men at Gay Pride San Jose, June 1978. All of the men are wearing buttons on their clothing. The man on the far right is Wayne Friday, political editor of the Bay Area Reporter, a free weekly newspaper serving the LGBT communities in the San Francisco Bay Area.